A component-based method for developing web applications - Montilva C., Jonas A.; Barrios A., Judith (Revista Colombiana de Computación, 2003)
We describe, in this paper, a component-based software engineering method for helping development teams to plan, organize, control, and develop web applications. The method is described in terms of three methodological elements: a product model that captures the architectural characteristics of web applications, a team model that describes the different roles to be played by the members of a team during the development of web applications, and a process model that integrates the managerial and technical activities that are required to develop componentized web applications of high quality. Keywords: Component-Based Software Engineering, Web Engineering, Web Information Systems